Decompression of Inflammatory Edema along with Endothelial Cell Therapy Expedites Regeneration after Renal Ischemia-Reperfusion Injury. Issue 11 (November 2013) - Herrler, Tanja; Wang, Hao; Tischer, Anne; Schupp, Nina; Lehner, Sebastian; Meyer, Andreas; Wallmichrath, Jens; Habicht, Antje; Mfarrej, Bechara; Anders, Hans-Joachim; Bartenstein, Peter; Jauch, Karl-Walter; et al.
Increased pressure due to postischemic edema aggravates renal ischemia-reperfusion injury (IRI). Prophylactic surgical decompression using microcapsulotomy improves kidney dysfunction after IRI. Supportive cell therapy in combination with microcapsulotomy might act synergistically protecting kidney function against IRI. The effects of therapeutic endothelial cell application alone and in combination with microcapsulotomy were investigated in a xenogenic murine model of 45-min warm renal ischemia. Renal function and perfusion were determined before as well as 2 and 18 days postischemia by 99m Tc-MAG3 imaging and laser Doppler. Histological analysis included H&E stains and immunohistology for endothelial marker MECA-32, cell proliferation marker Ki-67, and macrophage marker F4/80. Histomorphological changes were quantified using a tubular injury score. Ischemia of 45 min led to severe tissue damage and a significant decrease in renal function and perfusion. Microcapsulotomy and cell therapy alone had no significant effect on renal function, while only surgical decompression significantly increased blood flow in ischemic kidneys. However, the combination of both microcapsulotomy and cell therapy significantly improved kidney function and perfusion. Combination therapy significantly reduced morphological injury of ischemic kidneys as determined by a tubular injury score and MECA-32 staining. Macrophage infiltration evidenced by F4/80 staining was significantly reduced. The Ki-67 proliferation index was increased, suggesting a regenerative environment. While microcapsulotomy and cell therapy alone have limited effect on renal recovery after IRI, combination therapy showed synergistic improvement of renal function, perfusion, and structural damage. Microcapsulotomy may create a permissive environment for cell therapy to work.